A novel dynamic constitutive model for UHPC under projectile impact. (1st April 2023) - Zhou, Fei; Su, Qiong; Cheng, Yuehua; Wu, Hao
Highlights: New dynamic constitutive model of UHPC is established for projectile impact loading. Material parameters of established and KCC models are comprehensively calibrated. Projectile impact tests on semi-infinite and finite-depth targets are simulated. Superiority of new model over KCC model in predicting material response is verified. Abstract: Aimed at numerically predicting the impact resistance and damage pattern of ultra-high performance concrete (UHPC) under projectile impact, this study established a novel dynamic constitutive model for UHPC based on an improved Karagozian & Case concrete (KCC) model newly proposed by authors. Firstly, the established model is introduced, which considers the complex dynamic mechanical properties of UHPC, including the Lode-dependence, strain rate effect, compressive strain hardening and softening, tensile strain softening, volumetric compaction, and shear dilation. Particularly, a four-stage strain softening tensile damage model is adopted for UHPC. Then, the established model is embedded in the commercial hydrocode LS-DYNA as a user defined material model. According to the existing test data of UHPC, the failure surface, strain rate effect, equation of state, and damage model parameters are calibrated for the established model. For comparison, the parameters of the KCC model are also calibrated accordingly. To verify the calibrated material model parameters, single element tests are conducted under tensile and compressive loadings. Finally, the high velocity impact tests performed on both the semi-infinite targets and finite-depth panels with varying striking velocity are simulated, where the established model and the KCC model are respectively adopted for UHPC. It demonstrates that the established model reproduced the impact resistance and damage pattern of UHPC under projectile impact accurately, while the KCC model cannot reflect the dynamic response of UHPC satisfactorily.